(untitled) (Journal of Scientific Research, 2012)
Treatment of textile effluent, collected from Sattar Textile located at Chandra under Gazipur district, Bangladesh was carried out by chemical coagulation and precipitation method. The highly alkaline (pH=12.0) reddish orange colored effluent was characterized by chemical oxygen demand (COD) 1638 mg O2/L; total suspended solids (TSS) 9.76 g/L; total dissolved solids (TDS) 6.62 g/L and turbidly 31.24 FTU. In the present study, polyaluminium chloride (PAC) and SAFI (described in the results and discussions part) solutions were used as coagulants both individually and as their mixture at various ratios. As coagulation precipitation is highly pH sensitive, influence of pH was noted in each case. It was seen that the combined effect of both the coagulants is more effective than the individual effect of coagulants at a particular proportion at pH 6 for the removal of pollutional load from the effluent. The minimum dosages for the coagulants were worked out also from the initial beaker experiments. Finally, the effluent obtained from the large scale treatment was characterized for some effluent quality parameters and 90.17, 74.09 and 93.47% removal COD, TDS and turbidity were observed, respectively. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.10777 J. Sci. Res. 4 (3), 623-633 (2012)